Improvement of Andong Horseshoe Quality in Yogyakarta City to Support City Tourism - Alva Edy Tontowi; Mochammad Noer Ilman; Dawi Karomati Baroroh (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
The Zero Kilometer Point is an important route for andong horses in Yogyakarta City. The renovation and replacement of road material with andesite can cause horses to slip because the horseshoes have not been adjusted to the new road material. If neglected, it can harm the horses and its owners, reducing the tourism industry in Yogyakarta. On the other hand, horseshoes demand is still met by small and medium enterprises (SME) without a well-standardized system. After doing technical testing to the existing horseshoe design, several alternative solutions were obtained for horseshoe redesign (1) by adding rubber pads and (2) serrated without rubber pads. Based on analysis and testing, it was found that horseshoe with the addition of rubber by 40% was able to increase the friction value to 0.54 or 10% from the initial condition. Besides improving the productivity and quality of SME horseshoe products, several solutions should be considered, including (1) change the layout design of SME by implementing 5S lean six sigma principles and (2) apply new methods/technology to maintain the standardization of horseshoe product. Implementation of both solutions will guarantee not only the quality product but also SME production. It is hoped that all the improvements that have been made will increase the quantity and quality of horseshoe products. Then it will also be able to improve the image of Yogyakarta City as a tourist city.